Sweet corn yield response to alternate furrow irrigation methods under different planting densities in a semiarid climatic condition - Kashiani, Pedram; Saleh, Ghizan; Osman, Mohamad; Habibi, Davood (Academic Journals, 2011)
A field study was conducted to investigate sweet corn variety KCS 403 performance for yield and yield components under treatments of every furrow irrigation (EFI), semi-alternate furrow irrigation (SAFI) and alternate furrow irrigation (AFI), with different planting densities in shallow and deep groundwater regimes. Plots under SAFI were irrigated every other furrow from sowing till six weeks, followed by full irrigation on every furrow till the end of growing season. Plots under EFI were irrigated every furrow throughout the growth period, while those under AFI were irrigated every other furrow throughout growth period. Results showed significant effects of the three irrigation regimes for fresh ear yield, 1000-kernel weight, ear diameter, cob diameter, number of kernel rows per ear, number of kernels per row, number of kernels per ear (all at p ≤ 0.01), and fresh ear weight (p ≤ 0.05). However, there was no significant difference on the effects between EFI and SAFI for all the traits measured in the study. This indicates that yield and yield components of sweet corn under SAFI treatment were comparable with those under EFI. Unexpectedly, fresh ear yield and number of kernels per ear were found to be significantly higher under SAFI at the density of eight plants per m2 than the other irrigation treatment combinations. The results also revealed significant effects of planting densities for all the traits measured except fresh ear weight. Plants at lower density produced ears with higher quality, however the overall performance was found to be higher while the number of plants per unit area was higher. This might be due to the level of competition among the individual plants for water, sunlight and nutrients at the different planting densities. In general, sweet corn yield under SAFI at the density of eight plants per square meter was found to be same as those under EFI, with 30% less water supplied. It can be concluded that SAFI is a way to save water in arid and semi-arid areas where corn production relies heavily on repeated irrigation.